ROAD DAMAGE EVALUATION ON RIGID PAVEMENT WITH PAVEMENT CONDITION INDEX METHOD IN KLAKAH REJO-BENOWO ROAD, SURABAYA CITY, EAST JAVA - Mestuni, Welsi Buy; Hartatik, Nurani (Jurnal Teknik Sipil, 2023)
The research objective was to analyze the level and type of damage from every kind of damage on the Klakah Rejo Benowo road by calculating the rigid pavement condition index value and providing solutions. This study took the location of the Klakah Rejo-Benowo road section, Surabaya City"”data analysis by calculating the Deduct Value, m, TDV, CDV, and PCI. The research results state it was concluded that five types of damage occurred in Jalan Klakah Rejo-Benowo, Surabaya City. The types of damage are Grooves, Patches, Alligator Cracks, Weathering and Loose Granules, and Pits. Damage caused by high rainfall conditions ( 900mm/year) Daily Traffic Volume exceeds the provisions of the Binamarga. After analysis, it shows that the road pavement is in Moderate/Fair condition; field analysis results and values calculated using the PCI (Pavement Index Condition) method for damaged road conditions can provide recommendations for road repairs using the Asphalt Institute MS-17 method, namely patching and resurfacing. Based on the analysis of the road condition values obtained, the solution must be patched and re-coated so that water does not quickly seep into the road layer, which causes more severe road damage.